A word from our Editor-in-Chief: International Conference of NonconventionalTechnologies - ICNcT 2024 (Nonconventional Technologies Review, 2025)
National University of Science and Technology POLITEHNICA Bucharest, Romanian Association for Nonconventional Technologies – ARTN, The Academy of Romanian Scientists, Romanian Association for Alternative Technologies Sibiu – A.R.T.A. Sibiu, with the support of the Ministry of Research, Innovation and Digitization, have the honor to organize at National University of Science and Technology POLITEHNICA Bucharest during the 21st – 22nd November 2024, the International Conference of Nonconventional Technologies - ICNcT 2024.